The Life Functioning Scale: A Measurement Tool Developed to Assess the Physical Functioning Abilities of Community-Dwelling Adults Aged 50 Years or Older - Yunhwan Lee; Eunsaem Kim; Jihye Yun; Jaewon Choi; Jinhee Kim; Chang Won Won; Miji Kim; Soongnang Jang; Kyungwon Oh; Jihee Kim (Annals of Geriatric Medicine and Research)
Background This study aimed to develop an instrument for assessing physical functioning among adults aged 50 years or older living in the community. Methods Based on a review of various national health surveys and cohort studies, a 144-item bank was constructed for assessing physical functioning. Focus group interviews were conducted among adults aged 50 years or older to investigate their level of understanding of 60 selected items, followed by a pretest of the items on a nationally representative sample (n=508). The final 25-item questionnaire was tested on an independent sample (n=259) for validity and reliability based on classical test and item response theories. Predictive validity at the 6-month follow-up was tested in a separate sample (n=263). Results The newly developed Life Functioning (LF) scale assessed the dimensions of functional limitations, disabilities, and social activities. The scale satisfied a one-dimensionality assumption with good item fit and demonstrated criterion validity, construct validity, high internal consistency (Cronbach’s alpha=0.93), and test-retest reliability (intra-class correlation coefficient=0.84; 95% confidence interval, 0.76–0.89). The LF scale comprised 25 items with a total score ranging from 0 to 100. Higher scores indicated higher levels of functioning. The LF score was significantly associated with the Physical Functioning score at 6 months. Conclusion The LF scale was developed to assess the physical functioning of people in their late midlife or older. Future studies should test the instrument on a national sample and evaluate its application in diverse population subgroups.